¬¬Pengaruh Terpaan Berita Kebocoran Data Pengguna Tokopedia dan Terpaan E-Word of Mouth Terhadap Citra Tokopedia - Abigail Betsy Eliasta Roos; Djoko Setyabudi; Joyo Nur Suryanto Gono (Interaksi Online, 2021)
In early March 2020, there was a leak of data on Tokopedia users, with 91 million Tokopedia user data leaked and traded on the Dark Web. User data is sold for 5,000 US dollars (amounting to Rp74 million). The Tokopedia data leak event had a big impact on consumers whose data had been leaked to the dark web site. Successfully collected customer data includes names, e-mails, and passwords in one database. This news can have a big effect on consumer attitudes towards Tokopedia. Various responses from the public regarding the leakage of Tokopedia user data are quite large on social media. One of them social media is twitter. This study aims to determine the effect of news exposure of Tokopedia users' data leakage and word of mouth on the Tokopedia image. The theory used in this research is Uses and Effect Theory. To determine the sample, this study uses a non-probability sampling technique. The number of samples studied was 50 people with male / female characteristics, aged 18-40 years, in Indonesia and had received news of data leakage from Tokopedia users. The results showed that Tokopedia user data leakage exposure to Tokopedia's image had a significance value of 0.220 which means there is no significant relationship. Furthermore, e-word of mouth exposure with Tokopedia image has a significance value of 0.381 which means there is no significant relationship.